An interference cancellation algorithm for fourier-based and wavelet-based OFDM systems - Abdullah, Khaizuran; Neville, Katrina L.; Hussain, Zahir (2008)
An Interference Cancellation Algorithm (ICA) for both Fourier- and wavelet-based OFDM is proposed. In this study we investigated both an ideal case as well as a non-ideal case of our system. In the ideal case we assume the reference signal is an unwanted sinusoidal signal (the input to our ICA algorithm). In the non-ideal case, we assume the received OFDM signal is contaminated with sinusoidal interference. Simulation results performed at a SNR of 5d8 resulted in an error measurement of 0.01812 for wavelet OFDM and an error of approximately 0.03277 for Fourier-OFDM for the ideal case and for the nonideal case an error of 0.01817 was measured for wavelet-based OFDM and 0.03167 for Fourier-based OFDM. This indicates that the proposed leA exhibits outstanding performance since the results obtained in both cases are almost the same. The waveletbased OFDM outperformed the Fourier-based OFDM in both cases.